Opportunities for using blockchain in distributed solar energy projects. Issue 2 (1st November 2022) - Gunarathna, M A C L; Yang, R J; Jayasuriya, S; Wang, K; Samarasinghalage, T; Zang, Y
Abstract: The involvement of many stakeholders from diverse sectors throughout the distributed solar energy (DSE) project lifecycle and their discrete commitments to the project have lessened the stakeholder understanding in each other's contribution. Communication between the stakeholders is not continuous and systematic; thus, the project information is not well-communicated for accurate decision making. Therefore, DSE projects have not yet won the complete stakeholder trust and its adoption in the building industry is not yet fully accepted. This study aims at exploring the opportunities for using blockchain technology to reduce/eliminate the trust issues and communication gaps along the DSE lifecycle. The study conducts 50 semi-structured interviews with building and energy stakeholders to identify the issues/ limitations which (1) reduce the stakeholder trust on DSE technologies and applications and (2) generate communication gaps along the DSE project lifecycle. Findings reveal that most of the issues/ limitations occurred due to the unavailability of a common platform for communication and information sharing, unavailability of information, improper record keeping and limited information security. The unique features of blockchain technology such as (1) distributed ledger technology (DLT), (2) smart contracts, (3) token-based access control, and (4) automated consensus and forking can effectively eliminate the identified issues/ limitations by providing (1) information accuracy and reliability, (2) information security, (3) open access to project information, (4) systematic record keeping and (5) proper governance of the system. The outcome of this study provides a systematic approach to increase the quality of communication in DSE projects design and management.